Organisation and administration for business. - Whitehead, Geoffrey (Routledge library editions. Organizations : theory & behaviour, 2013)
This book provides a comprehensive introduction to business organisation and administration. Written in a straightforward, readable style this textbook covers all the major aspects of the subject. Starting with the organisational background it goes on to cover the functions of the important departments within the firm, the role of the administrative officer, and other areas of knowledge vital to the smooth running of a business. There are self-assessment questions at the end of each section, past exam questions, study and exam tips and a full index.